(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article studies the spread of fungal-parasitic diseases on cereal plants of Kashkadarya region. From diseases of cultivated and wild- growing cereals m Kashkadarya region. The most important are smut, rust, powdery mildew and septoria.